History Of Indonesia's Islamic Educational Institutions In A Political Framework - Zetty Azizatun Ni’mah; Ahmad Rifa'i (Pustaka Peradaban, 2022)
Education and politics are like inseparable currencies. The development of Islamic education in Indonesia, even across history, cannot be separated from political penetration. Politics makes regulation of policies in Islamic education. The rapid development of Islamic education depends on the intimate relationship between Islamic education figures and the government. In the history of the colonial period, the politics of setting policies on Islamic institutions tended to be discriminatory and gave benefits to the colonialists. During the old order era, the presence of the Ministry of Religion on January 3, 1946 , politically fought for Islamic education in Indonesia, which was based on the aspirations of Muslims so that religious education should be taught in schools, in addition to the development of madrasas themselves. During the Old Order era, there was already concern for madrasas, but the political conditions dominated by NASAKOM's ideas caused madrasas to not develop significantly. The New Order era was a government that gave a positive and constructive response to the development of Islamic educational institutions, madrasas, which in the end gave recognition by making madrasas part of the national education system. And in the current era, Islamic educational institutions in general and madrasas in particular have become the focus of many people because in addition to the same curriculum as the one in the Ministry of National Education, they are considered capable of providing internalization of religious character and competing with other public education institutions.